Branding dan Pemanfaatan Media Sosial dalam Meningkatkan Penjualan Nasi Uduk Ayam Geprek ECO - Aurellius Krisna Putra; Andreas Candra; Claudius Kristian Hery; Illona Hartanto; Jennifer Huang; Jemmy Jemmy; Lauren MI. Aidelin; Santi Rimadias (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The growth of the digital era has brought changes in the operations of Micro, Small, and Medium Enterprises (MSMEs). The key to the success of MSMEs today can be supported by branding and the use of social media. The use of social media is still not optimal. However, business actors already have a fairly inherent branding, namely ECO which means